Wearable, modular and intelligent sensor laboratory - Hill, M.; Hoena, B.t; Kilian, W.; Odenwald, S. (Procedia Engineering, 2016)
In this paper, a modular sensor system for recording pressure distribution, 3D-acceleration, 3D-angular velocity, temperature and humidity in a shoe insole is presented. The intelligent sensor-insole is a measurement system that can be used in medical and sport related fields. Integrated sensors record physical parameters such as acceleration and or pressure which can also be used to trigger an additional feedback system. Through intelligent and high performant electronics, the feedback system is able to operate in real time. The combination of individually miniaturized systems, wireless data transmissions and a rechargeable battery enables the system for a wide field of application such as fall prevention, training analysis and motion optimization. Robust and miniaturized hardware components as well as wireless communication technology enable real-time processing of data. Measurement data can be stored locally on the measurement device for post analysis, as well as visualized on connected mobile devices such as smartphones or tablets. Aiming at using the system as a mobile and easy-to-use lab, both under laboratory conditions and in field. Applications like gait- and running analysis outside the laboratory, fall detection and activity monitoring in a home environment are possible. Due to the high performance of the system, the data pre-processing can be performed on the embedded system. Because the system supports wireless connections, it is possible to combine several of the systems to build a sensor network. Furthermore, it is possible to transmit the collected data to a cloud. The system will provide the measured data in different levels of complexity. For instance, the system is able to evaluate the data automatically and provide the results to experts such as physicians and coaches.